A method for preparing elastic silicon-carbon negative electrode composite material
By using a combination of micro-expanded elastic graphite powder and water-based binder in silicon carbon negative electrode materials, the problem of volume expansion of silicon carbon negative electrode materials during charging and discharging is solved, the circulation performance and capacity of lithium batteries are improved, and the cost is reduced , and simplifies the process and extends battery life.
Patent Information
- Application Number
- CN202211545588.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-05
AI Technical Summary
The existing silicon carbon anode materials have structural damage and phase separation due to the volume expansion of silicon during charging and discharging, resulting in poor battery stability and shortened effective life.
Using the combination of micro-expanded elastic graphite powder, silicon powder and graphite powder, the oxidant aqueous solution is sprayed and stirred in a mist, and then micro-expanded. Combined with aqueous binder and sintering heat treatment, an elastic silicon-carbon negative electrode composite material is prepared. , adjust the binding force of silicon and carbon to reduce the negative effect of expansion.
It effectively improves the circulation performance and capacity of lithium batteries, reduces costs, simplifies the preparation process, and extends the effective life of the battery.
Smart Images

Figure BDA0003979663500000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy battery materials, and in particular relates to a method for preparing an elastic silicon-carbon negative electrode composite material. Background Art
[0002] The development of silicon-based negative electrode materials is of great significance for promoting the progress of my country's next generation of high-energy density lithium-ion batteries and new energy electric vehicle technologies and enhancing my country's core scientific and technological competitiveness. The theoretical capacity of silicon is as high as 4200mAh / g, which is more than ten times the theoretical capacity of 372mAh / g of graphite, the current mainstream negative electrode material for lithium-ion batteries. In addition, silicon has a low lithium deintercalation voltage (<0.5V), high safety, abundant sources, and low prices. However, during the battery charging and discharging process, the lithium deintercalation reaction of silicon will be accompanied by a huge volume change (>300%), causing the destruction of the material structure and mechanical pulverization, resulting in the separation of electrode materials and electrode materials from the current collector, and then losing electrical contact, causing the capacity to decay rapidly, the cycle performance to deteriorate, and the effective life of the battery to be greatly shortened.
[0003] At present, there are many and diverse technologies and methods for preparing silicon-carbon negative electrodes, with complex processes, high costs and unstable performance. The ball milling method is used to compound silicon and graphite. Although it can partially meet application requirements in terms of electrochemical performance and economic benefits, its main defect is that it still cannot effectively alleviate the serious volume effect of silicon during the charging and discharging process, which leads to the volume expansion of electrode materials. The binding force between silicon and carbon is poor, and phase separation is prone to occur during the charging and discharging process, resulting in poor battery stability and shortened effective life. The actual use effect is still far from the expected value, resulting in slow market development of silicon-carbon negative electrodes. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an elastic silicon-carbon negative electrode composite material to solve the problem that the existing silicon-carbon negative electrode material will experience volume expansion of the electrode material during the charging and discharging process, resulting in poor bonding between silicon and carbon, easy phase separation during the charging and discharging process, resulting in poor battery stability and shortened effective life.
[0005] In order to achieve the above object, the technical solution of the present invention is: a method for preparing an elastic silicon-carbon negative electrode composite material, comprising:
[0006] Prepare raw materials, the raw materials include silicon powder, graphite powder, micro-expanded elastic graphite powder and water-based binder, the preparation method of micro-expanded elastic graphite powder is: spray the graphite powder with an oxidant aqueous solution in a mist form and stir it, put the sprayed and stirred graphite powder into a crucible, then push the crucible into an electric furnace to micro-expand the graphite, then take out the crucible and cool it, and take out the micro-expanded elastic graphite powder in the crucible;
[0007] Raw material ratio: silicon powder 10-20wt%, micro-expanded elastic graphite powder 10-50wt%, graphite powder 30-70wt%, silicon powder, graphite powder and micro-expanded elastic graphite powder total 100wt%, water-based binder accounts for 15-20wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder;
[0008] Mixing and kneading: First, dry-mix the proportioned silicon powder, graphite powder and micro-expanded elastic graphite powder. After the dry-mixing is completed, add the proportioned water-based binder and mix to form a colloidal phase;
[0009] Sheet rolling: the colloid phase after kneading is sheeted to form a sheet;
[0010] Sintering heat treatment: put the rolled sheet into a small crucible, then put the small crucible into a large crucible, and push the large crucible into an electric furnace for sintering heat treatment; after the heat treatment is completed, an elastic silicon-carbon negative electrode composite material is obtained.
[0011] Furthermore, the oxidant concentration in the oxidant aqueous solution is 5-30%, and the oxidant is a composition of at least two of the following substances: H2O2, KMnO4, K2Cr2O7, CH2O2, HClO4, CH3COOH (HAc), and H3PO4.
[0012] Furthermore, the preparation method of the micro-expanded elastic graphite powder is specifically as follows: the graphite powder is sprayed with an oxidant aqueous solution in a mist form and stirred, and the graphite powder is in a stirring and tumbling state during the spraying process; the spraying and stirring time is 30-60 minutes, and after stopping the spraying of the oxidant aqueous solution, the graphite powder is continued to be stirred for 20-50 minutes; the sprayed and stirred graphite powder is loaded into an uncovered crucible, and then the crucible is pushed into an electric furnace at 700-900°C for 1-5 minutes to make the graphite micro-expanded, and then the crucible is taken out and cooled, and the micro-expanded elastic graphite powder in the crucible is taken out; finally, the micro-expanded elastic graphite is subjected to a graphitization temperature heat treatment.
[0013] Furthermore, the particle size of graphite powder is 200-400 mesh, and the particle size of silicon powder is 400-600 mesh; the processing process of silicon powder is: soaking silicon powder in a solution prepared by industrial alcohol and acetone, and stirring for 20-40 minutes, and then filtering and drying the silicon powder.
[0014] Furthermore, the aqueous adhesive bonding matrix is at least one of molasses, sucrose, glucose and plant starch, and water is added and stirred evenly to form an aqueous adhesive.
[0015] Further, kneading treatment: firstly, dry-mix the proportioned silicon powder, graphite powder and micro-expanded elastic graphite powder evenly for no less than 10 minutes. After the dry-mixing is completed, add the proportioned water-based binder, stir and knead repeatedly for 30-40 minutes at a kneading temperature of 70±10°C to form a colloidal phase.
[0016] Further, sheeting treatment: the colloid phase after the kneading treatment is sheeted, the roller temperature is 70-100°C, and the sheeting is repeated for more than 3 times. The sheet thickness is 3-5mm, and it is cut into 30-40mm square sheet materials.
[0017] Further, sintering heat treatment is performed: the rolled sheet is placed into a small crucible and covered with a lid, and then the small crucible is placed into a large crucible; calcined petroleum coke powder is filled into the large crucible and covered with a lid, and the large crucible is pushed into an electric furnace for sintering heat treatment; after the heat treatment is completed, an elastic silicon-carbon negative electrode composite material is obtained.
[0018] Furthermore, the sintering temperature rise curve is carried out in 5 stages:
[0019] Stage 1: room temperature - 250°C, heating rate 3-5°C / min;
[0020] The second stage: 250-450℃, heating rate is 1-2℃ / min;
[0021] The third stage: 450-650℃, heating rate is 2-3℃ / min;
[0022] The fourth stage: 650-850℃, heating rate is 3-4℃ / min;
[0023] The fifth stage: 850-1000℃, heating rate is 4-5℃ / min; keep the highest temperature at 1000℃ for 1 hour, turn off the power to stop heating, and let the furnace cool freely to room temperature before the product is taken out of the furnace.
[0024] The beneficial effect of this technical solution is that the present invention solves the urgent problem that the silicon-carbon negative electrode of lithium batteries is easy to expand during the electrochemical process, which leads to the degradation of battery efficiency and rapid failure. The negative effect of silicon component expansion is effectively eliminated and reduced by adjusting the ratio between compressible and expandable components inside the silicon-carbon negative electrode ingredients. This is a pioneering work. The silicon-carbon negative electrode composite material of the present invention makes the lithium battery have high specific capacity, good cycle performance, low cost and simple preparation process. DETAILED DESCRIPTION
[0025] The following is further described in detail through specific implementation methods:
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1
[0028] A method for preparing an elastic silicon-carbon negative electrode composite material comprises the following steps:
[0029] S1: Prepare raw materials, including silicon powder, graphite powder, micro-expanded elastic graphite powder and water-based binder.
[0030] The processing process of silicon powder is as follows: soak metal silicon powder (400-600 mesh) in a solution prepared by industrial alcohol and acetone, and stir for 30 minutes. The main function of this process is to remove stains on the surface of silicon powder particles and increase surface energy. Then the treated metal silicon powder is filtered and dried for standby use.
[0031] The graphite powder is artificial graphite powder (200-400 mesh) specially used for graphite negative electrode of lithium battery, which is dried for use.
[0032] The preparation method of micro-expanded elastic graphite powder is as follows: natural flake graphite powder (200 mesh, purity ≥90%) with a carbon content of ≥99% is sprayed with a 15-25% oxidant aqueous solution in a mist form and stirred (the oxidant is a composition of at least two of the following substances: H2O2, KMnO4, K2Cr2O7, CH2O2, HClO4, CH3COOH (HAc), H3PO4, and the oxidant composition in this embodiment is: H2O2 / CH3COOH=1). During the spraying process, the graphite powder is always in a stirring and tumbling state to ensure that the graphite powder is fully in contact with the oxidant aqueous solution. The spraying and stirring time is 45 minutes. After the spraying of the oxidant aqueous solution is stopped , the stirrer continues to stir the graphite powder for 40 minutes; the graphite powder after spraying and stirring is loaded into a porcelain crucible without a cover, and then the crucible is pushed into an electric furnace at 800°C for 1-2 minutes. The graphite powder has been slightly expanded according to the design requirements, and then the crucible is taken out and cooled, and the slightly expanded elastic graphite powder in the crucible is taken out; in order to improve the purity and conductivity of the slightly expanded elastic graphite, the slightly expanded elastic graphite is finally subjected to a heat treatment at a graphitization temperature (≥2500°C). The obtained slightly expanded elastic graphite powder has a powder resistivity of ≤100μΩm, a true density of ≥2.22g / cm3, a particle size of 100-200 mesh, and has excellent reversible properties of compression and rebound, and also has excellent conductive properties.
[0033] The aqueous adhesive bonding matrix is at least one of molasses, sucrose, glucose and plant starch, and in this embodiment, it is sucrose. Water is added and stirred evenly to form an aqueous adhesive. The amount of water is based on completely dissolving the bonding matrix but not exceeding the amount.
[0034] S2: Raw material ratio: silicon powder 20wt%, micro-expanded elastic graphite powder 20wt%, graphite powder 60wt%, and water-based binder accounts for 15wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder.
[0035] S3: kneading treatment: firstly, add the proportioned silicon powder, graphite powder and micro-expanded elastic graphite powder into a small double-twister kneading machine and dry-mix them for 10 minutes. After the dry-mixing is completed, add the proportioned water-based binder, stir and knead repeatedly for 30 minutes, and the kneading temperature is 70±10°C to form a colloidal phase;
[0036] S4: sheeting: the colloid phase after kneading is sheeted using a temperature-adjustable sheeting machine, the roller temperature is 80±10°C, the speed is 40 rpm, and the sheeting is repeated 4 times. The sheet thickness is 3-5mm, and it is cut into 30-40mm square sheet materials;
[0037] S5: Sintering heat treatment: put the sheet after rolling into a high-temperature resistant stainless steel small crucible and cover it with a lid, then put the small crucible into a large refractory crucible; fill the large crucible with calcined petroleum coke powder (less than 0.5mm), bury the stainless crucible in the coke particles (the thickness of the top coke particles is greater than 80mm), and cover the large crucible with a lid, so as to ensure that the sheet material is not oxidized during the high-temperature sintering heat treatment process in the electric furnace. The large crucible is pushed into an electric furnace for sintering heat treatment; the sintering heating curve is heated according to 5 stages: the first stage: room temperature-250°C, the heating rate is 3-5°C / min; the second stage: 250-450°C, the heating rate is 1-2°C / min; the third stage: 450-650°C, the heating rate is 2-3°C / min; the fourth stage: 650-850°C, the heating rate is 3-4°C / min; the fifth stage: 850-1000°C, the heating rate is 4-5°C / min; the highest temperature is 1000°C and kept for 1 hour, the power is turned off to stop heating, the electric furnace is cooled freely to room temperature, and the product is taken out of the furnace, that is, the elastic silicon-carbon negative electrode composite material is obtained.
[0038] The sheet-like elastic silicon-carbon negative electrode composite material prepared in this example was crushed and sieved, and the obtained fine powder was subjected to relevant performance tests; the fine powder of the elastic silicon-carbon composite negative electrode material was made into a lithium-ion battery negative electrode according to a general technical method, and then assembled into a square battery, and various electrochemical performance tests were carried out. The relevant test data are shown in Example 1 in Table 1.
[0039] Embodiment 2
[0040] A method for preparing an elastic silicon-carbon negative electrode composite material. The difference between this embodiment and embodiment 1 is only that: 15wt% silicon powder, 20wt% micro-expanded elastic graphite powder, 65wt% graphite powder, and an aqueous binder accounts for 15wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder.
[0041] The sheet-like elastic silicon-carbon negative electrode composite material prepared in this example was crushed and sieved, and the obtained fine powder was subjected to relevant performance tests; the fine powder of the elastic silicon-carbon composite negative electrode material was made into a lithium-ion battery negative electrode according to a general technical method, and then assembled into a square battery, and various electrochemical performance tests were carried out. The relevant test data are shown in Example 2 in Table 1.
[0042] Embodiment 3
[0043] A method for preparing an elastic silicon-carbon negative electrode composite material. The difference between this embodiment and embodiment 1 is only that: 10wt% silicon powder, 20wt% micro-expanded elastic graphite powder, 70wt% graphite powder, and an aqueous binder accounts for 15wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder.
[0044] The sheet-like elastic silicon-carbon negative electrode composite material prepared in this example was crushed and sieved, and the obtained fine powder was subjected to relevant performance tests; the fine powder of the elastic silicon-carbon composite negative electrode material was made into a lithium-ion battery negative electrode according to a general technical method, and then assembled into a square battery, and various electrochemical performance tests were carried out. The relevant test data can be seen in Example 3 in Table 1.
[0045] Embodiment 4
[0046] A method for preparing an elastic silicon-carbon negative electrode composite material. The difference between this embodiment and embodiment 1 is only that: 20wt% silicon powder, 30wt% micro-expanded elastic graphite powder, 50wt% graphite powder, and an aqueous binder accounts for 15wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder.
[0047] The sheet-like elastic silicon-carbon negative electrode composite material prepared in this example was crushed and sieved, and the obtained fine powder was subjected to relevant performance tests; the fine powder of the elastic silicon-carbon composite negative electrode material was made into a lithium-ion battery negative electrode according to a general technical method, and then assembled into a square battery, and various electrochemical performance tests were carried out. The relevant test data are shown in Example 4 in Table 1.
[0048] Embodiment 5
[0049] A method for preparing an elastic silicon-carbon negative electrode composite material. The difference between this embodiment and embodiment 1 is only that: 20wt% silicon powder, 40wt% micro-expanded elastic graphite powder, 40wt% graphite powder, and an aqueous binder accounts for 15wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder.
[0050] The sheet-like elastic silicon-carbon negative electrode composite material prepared in this example was crushed and sieved, and the obtained fine powder was subjected to relevant performance tests; the fine powder of the elastic silicon-carbon composite negative electrode material was made into a lithium-ion battery negative electrode according to a general technical method, and then assembled into a square battery, and various electrochemical performance tests were carried out. The relevant test data can be seen in Example 5 in Table 1.
[0051] Embodiment 6
[0052] A method for preparing an elastic silicon-carbon negative electrode composite material. The difference between this embodiment and embodiment 1 is only that: 20wt% silicon powder, 50wt% micro-expanded elastic graphite powder, 30wt% graphite powder, and an aqueous binder accounts for 15wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder.
[0053] The sheet-like elastic silicon-carbon negative electrode composite material prepared in this example was crushed and sieved, and the obtained fine powder was subjected to relevant performance tests; the fine powder of the elastic silicon-carbon composite negative electrode material was made into a lithium-ion battery negative electrode according to a general technical method, and then assembled into a square battery, and various electrochemical performance tests were carried out. The relevant test data can be seen in Example 6 in Table 1.
[0054] Comparative Example
[0055] The formula does not use the self-developed micro-expanded elastic graphite powder raw material, and all commercially available negative electrode graphite powder ingredients are used. The raw material ratio is: 20wt% silicon powder, 80wt% graphite powder, and the water-based binder accounts for 15wt% of the total amount of silicon powder and graphite powder. The relevant test data is shown in the comparative example in Table 1.
[0056] Table 1 Summary of comprehensive test data of 7 samples in Examples 1 to 6 and Comparative Example
[0057]
[0058] In Examples 1 to 6, micro-expanded elastic graphite powder is added, and in the comparative example, no micro-expanded elastic graphite powder is added, resulting in a rapid and significant decrease in the cycle specific capacity in the comparative example. After 500 cycles, the battery capacity retention rate is only 60.5%, and the expansion rate in the thickness direction of the assembled battery is 5.7%, indicating that the blank sample has the worst comprehensive performance. Therefore, it can be seen from Table 1 that the silicon-carbon negative electrode composite material prepared by the samples of Examples 1 to 6 has good cycle performance, high specific capacity, simple preparation process and low cost.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0060] The above is only an embodiment of the present invention. The common sense such as the known specific structure and characteristics in the scheme is not described in detail here. The ordinary technicians in the relevant field know all the common technical knowledge in the technical field of the invention before the application date or priority date, can know all the existing technologies in the field, and have the ability to apply the conventional experimental means before that date. The ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the protection scope of the present invention, which will not affect the effect of the implementation of the present invention and the practicality of the patent. The protection scope required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing an elastic silicon-carbon negative electrode composite material, characterized in that: include Prepare raw materials, which include silicon powder, graphite powder, micro-expanded elastic graphite powder and water-based binder. The preparation method of micro-expanded elastic graphite powder is as follows: spray the graphite powder with an oxidant aqueous solution in a mist form and stir it, and the graphite powder is in a stirring and tumbling state during the spraying process; the spraying and stirring time is 30-60 minutes, and after stopping the spraying of the oxidant aqueous solution, continue to stir the graphite powder for 20-50 minutes; put the sprayed and stirred graphite powder into an uncovered crucible, and then push the crucible into an electric furnace at 700-900°C for 1-5 minutes to make the graphite micro-expanded, then take out the crucible and cool it, and take out the micro-expanded elastic graphite powder in the crucible; finally, heat treat the micro-expanded elastic graphite at a graphitization temperature, and the temperature is ≥2500°C; Raw material ratio: 10-20 wt% silicon powder, 10-50 wt% micro-expanded elastic graphite powder, 30-70 wt% graphite powder, silicon powder, graphite powder and micro-expanded elastic graphite powder total 100 wt%, water-based binder accounts for 15-20 wt% of the total amount of silicon powder, graphite powder and micro-expanded elastic graphite powder; Mixing and kneading: First, dry-mix the proportioned silicon powder, graphite powder and micro-expanded elastic graphite powder. After the dry-mixing is completed, add the proportioned water-based binder and mix to form a colloidal phase; Sheet rolling: the colloid phase after kneading is sheeted to form a sheet; Sintering heat treatment: put the rolled sheet into a small crucible and cover it with a lid, then put the small crucible into a large crucible; fill the large crucible with calcined petroleum coke powder particles, bury the small crucible in the coke powder particles, cover it with a lid, and push the large crucible into an electric furnace for sintering heat treatment; after the heat treatment is completed, an elastic silicon-carbon negative electrode composite material is obtained.
2. The method for preparing an elastic silicon-carbon negative electrode composite material according to claim 1, characterized in that: The oxidant concentration in the oxidant aqueous solution is 5-30%, and the oxidant is a composition of at least two of the following substances: H2O2, KMnO4, K2Cr2O7, CH2O2, HClO4, CH3COOH (HAc), and H3PO4.
3. The method for preparing an elastic silicon-carbon negative electrode composite material according to claim 1, characterized in that: The particle size of graphite powder is 200-400 mesh, and the particle size of silicon powder is 400-600 mesh; the processing process of silicon powder is: soak the silicon powder in a solution prepared by industrial alcohol and acetone, and stir for 20-40 minutes, then filter and dry the silicon powder.
4. The method for preparing an elastic silicon-carbon negative electrode composite material according to claim 1, characterized in that: The bonding matrix of the aqueous adhesive is at least one of molasses, sucrose, glucose and plant starch, and water is added and stirred evenly to form an aqueous adhesive.
5. The method for preparing an elastic silicon-carbon negative electrode composite material according to claim 1, characterized in that: Mixing and kneading treatment: First, dry-mix the proportioned silicon powder, graphite powder and micro-expanded elastic graphite powder evenly for no less than 10 minutes. After the dry mixing is completed, add the proportioned water-based binder, stir and knead repeatedly for 30-40 minutes at a kneading temperature of 70±10°C to form a colloidal phase.
6. The method for preparing an elastic silicon-carbon negative electrode composite material according to claim 1, characterized in that: Rolling treatment: Roll the colloid after kneading treatment, the roller temperature is 70-100℃, and the rolling is repeated for more than 3 times. The thickness of the rolled sheet is 3-5mm, and it is cut into 30-40mm square sheet materials.
7. The method for preparing an elastic silicon-carbon negative electrode composite material according to claim 1, characterized in that: The sintering heating curve is heated in 5 stages: The first stage: room temperature - 250 ° C, heating rate is 3-5 ° C / min; The second stage: 250-450℃, heating rate is 1-2℃ / min; The third stage: 450-650℃, heating rate is 2-3℃ / min; The fourth stage: 650-850℃, heating rate is 3-4℃ / min; The fifth stage: 850-1000℃, heating rate is 4-5℃ / min; keep the highest temperature at 1000℃ for 1 hour, turn off the power to stop heating, and let the furnace cool freely to room temperature before the product is taken out of the furnace.
Citation Information
Patent Citations
Lithium-ion battery silicon-carbon anode material and preparation method thereof
CN103199252A
Method for preparing expanded microcrystal graphite material from microcrystal graphite
CN104556022A
